INTERACTIVE TRAINING METHODS IN RUSSIAN LANGUAGE AND LITERATURE LESSONS (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article discusses one of the ways to modernize education on a competency-based basis, namely through the use of interactive forms of teaching in teaching. interactive teaching methods provide solutions to educational problems in various aspects. Mastery of interactive learning technology contributes to the development of student qualities that meet the requirements specified in the new generation of state standards.